R4D WEEK 2010_team building activities - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
All works without play makes Jack a doll boy, In this video The IITA R4D Week engaged its scientist in series of games to illustrate the efficiency of team work (R4D 2010 TEAM BUILDING ACTIVITIES)